Oscillation of the Ionosphere at Planetary‐Wave Periods. Issue 9 (8th September 2018) - Forbes, J. M.; Maute, A.; Zhang, X.; Hagan, M. E.
Abstract: F‐region ionospheric oscillations at planetary‐wave (PW) periods (2–20 days) are investigated, with primary focus on those oscillations transmitted to the ionosphere by PW modulation of the vertically propagating tidal spectrum. Tidal effects are isolated by specifically designed numerical experiments performed with the National Center for Atmospheric Research thermosphere‐ionosphere‐electrodynamics general circulation model for October 2009, when familiar PW and tides are present in the model. Longitude versus day‐of‐month perturbations in topside F‐region electron density (Ne) of order ±30–50% at PW periods occur as a result of PW‐modulated tides. At a given height, these oscillations are mainly due to vertical oscillations in the F layer of order ±15–40 km. These vertical movements are diagnosed in terms of changes in the F2‐layer peak height, ΔhmF2, which are driven by the vertical projections of E × B drifts and field‐aligned in situ neutral winds. E × B drifts dominate at the magnetic equator, while the two sources play more equal roles between 20° and 40° magnetic latitudes in each hemisphere. The in situ neutral wind effect arises from vertical propagation of PW‐modulated tides, whereas the E × B drifts originate from dynamo‐generated electric fields produced by the E‐region component of the same wind field; the former represents a new coupling mechanism for production of ionospheric oscillations at PW periods. Roughly half the above‐mentioned variability in Ne and hmF2 is associated with zonally symmetric (S0) oscillations, which contribute at about half the level of low‐level magnetic activity during October 2009. The thermosphere‐ionosphere‐electrodynamics general circulation model simulates the S0 oscillations in Ne observed from the CHAMP satellite well during this period and reveals that S0 oscillations in E × B play a significant role in driving S0 oscillations in ΔhmF2, in addition to neutral winds. Key Points: Ionospheric oscillations occur at planetary‐wave (PW) periods (2–20 days) due to PW modulation of the upward‐propagating tidal spectrum A new mechanism for PW coupling in the atmosphere‐ionosphere system is discovered Zonally symmetric oscillations account for roughly half the ionospheric perturbations at PW periods